The Journey to Sustainable Participation in Physical Activity for Adolescents Living with Cerebral Palsy - Gaela Kilgour; Ngaire Susan Stott; Michael Steele; Brooke Adair; Amy Hogan; Christine Imms (MDPI AG, 2023)
Purpose: To understand adolescents' and their parents' perspectives on 'being active', this study explored the experience of participation in physical activity (PA), the role of long-term participation in PA, and the importance of remaining active for life. Methods: Eight ambulant adolescents with CP (aged 11-16 years, seven male) participated in a high-level mobility programme twice per week for 12 weeks. Guided using interpretive description, adolescents and 12 of their parents were interviewed before, after and nine months following the programme. Thirty-eight interviews were coded, analysed, and interpreted, informed by audit information, reflective journaling, and team discussions. Results: Adolescents and their parents highly value being active now and into adulthood. Sustainable participation in PA requires adolescents and families to navigate complex environments (interpersonal, organisational, community, and policy). Core themes were: 'Just Doing it', 'Getting the Mix Right' (right people, right place, right time), 'Balancing the Continua' and 'Navigating the Systems'. The continua involved balancing intra-personal attributes: 'I will try anything' through to 'I will do it if I want to' and 'It's OK to be different' through to 'It sucks being disabled'. Conclusions: The journey to sustainable participation was complex and dynamic. Experiences of successful journeys are needed to help adolescents with CP "stay on track" to sustainable participation.